2014
DOI: 10.1007/s10212-014-0235-4
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and teachers’ perceptions of quality in Portuguese childcare classrooms

Abstract: The main goal of this study was to examine parents' and teachers' perceptions of quality in early childhood education for toddlers in Portugal. A total of 110 parents and 110 teachers participated in the study, rating the importance of specific quality criteria and assessing childcare classrooms, based on the Infant/Toddler Environment Rating Scale Parent Questionnaire (ITERS-RPQ) and on the Infant/Toddler Environment Rating Scale Teacher Questionnaire (ITERS-RTQ), respectively. The same quality items were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
0
21
1
1
Order By: Relevance
“…It appears that the social and emotional components of relationships are considered crucial and intrinsically valued by the caregivers. Barros and Leal (2014) found that Although in this study the average scores for Relational Climate were higher than those found for Facilitated Exploration and Early Language Support, they were in the medium range of quality, suggesting that there is still room for improvement.…”
Section: Discussioncontrasting
confidence: 80%
“…It appears that the social and emotional components of relationships are considered crucial and intrinsically valued by the caregivers. Barros and Leal (2014) found that Although in this study the average scores for Relational Climate were higher than those found for Facilitated Exploration and Early Language Support, they were in the medium range of quality, suggesting that there is still room for improvement.…”
Section: Discussioncontrasting
confidence: 80%
“…For instance, measures of child engagement with toys and other materials, such as the Engagement Quality Observation System (EQual III; McWilliam & de Kruif, 1998), can provide relevant information, considering associations between process quality and child engagement (e.g, Aguiar & McWilliam, 2012;Raspa, McWilliam, & Ridley, 2001). The three measures used in the present study were not originally developed in Portugal, but two of them have been extensively used in Portugal, with findings indicating their adequacy to the Portuguese child care settings (Barros & Aguiar, 2010;Barros & Leal, 2015;Cadima et al, 2012;Cryer et al, 1999). Although this is the first Portuguese study that used the CLASS-Infant, the training procedure was conducted in close collaboration with one of the authors of the scale.…”
Section: Limitations and Future Considerationsmentioning
confidence: 99%
“…To our knowledge, there is only one study which focuses on reported quality levels and also considers the ECEC professionals' assessments. The study by Barros and Leal (2015) is based on a Portuguese sample and shows that parents and ECEC professionals overestimate quality in comparison to experts but that there is a higher correlation between professionals' and experts' ratings than between parents' and professionals' ratings. Thus, they find information asymmetries but do not analyze them more in-depth.…”
Section: Previous Studies and Differences In Information Asymmetriesmentioning
confidence: 99%